Comparison of D2 versus D1 gastrectomy in Kashmiri patients in a tertiary care cancer centre - Younis, Mohamad; Yousuf, Adfar; Ahmad, Syed Nisar; Vane, Ajay (International Surgery Journal, 2022)
Background: The aim of this study was to compare the clinical outcomes, survival, morbidity and mortality of D1 and D2 gastrectomy in Kashmiri population in a high-volume tertiary care centre. Methods: Data were collected retrospectively from the prospective database maintained by Department of Surgical Gastroenterology at SKIMS, Kashmir India. We did direct comparison of D1 and D2 gastrectomy in gastric cancer patients who underwent surgery between January 2016 to December 2021 and fulfilled the eligibility criteria. A total of 98 patients were included in the study of which 46 underwent a D1 gastrectomy and 52 underwent a D2 gastrectomy. Results: Male-female ratio was 3:1 in both groups with a mean age of 61 years. There was no significant difference in terms of age or gender between D1 and D2 groups (p>0.05). The mean number of harvested lymph nodes (LN) was (7±1.9) in the D1 group compared to (27.6±10.1) the D2 group (p=0.001). Average hospital stay was comparable in both groups. The median survival was 26 months for the D2 and 19 months for the D1 group (p≤0.01). The survival in the D2 group was significantly higher than in the D1 group. There was no difference in postoperative complications between two groups in our study. Conclusions: our study indicates that D2 gastrectomy should be the standard of treatment for advanced stage II /III disease as it improves the survival outcome in these patients without affecting overall hospital stay, morbidity and mortality.